Caracterização molecular de Bursaphelenchus cocophilus e controle de Meloidogyne incognita por moléculas orgânicas voláteis - Silva, Arinaldo Pereira da (2015)
Plant parasitic nematodes, such as Meloidogyne incognita and Bursaphelenchus cocophilus, cause serious losses in the world agriculture. M. incognita is an important pathogenic nematode in various agricultural commodities and its control is required to improve profit. Due to increased worries to the environment contamination and the toxicity to mammals caused by highly toxic agrochemicals used in managing plant parasitic nematodes, new strategies and products, less damaging to the environment, have been searched. The volatiles present potential to be used substituting the currently commercialized pesticides since they have demonstrated high nematicidal capacity and/or nematostatic. Thirty molecules were gathered to be evaluated as volatile nematicide to second stage juveniles (J2) and eggs of M. incognita. In the J2 exposition test for 24 hours to the volatiles, nineteen molecules caused 80% J2 immobility of M. incognita. The J2 infectivity and reproduction after volatile exposure showed reduction of gall and number of eggs/gr of roots at the same proportion that occurred the reduction of J2 mobility. The most toxic molecules, benzaldehyde, hexyl alcohol and 3-octanol were used in the assay of time exposition to volatile molecules. When J2 was exposed by only one hour to the volatile of benzaldehyde occurred 100% J2 immobility and great reduction of infectivity and reproduction of exposed M. incognita J2 which was only reached by hexyl alcohol and 3-octanol after five hours the exposition. B. cocophilus causes severe damage and losses in Palmae crops, however studies on species molecular characterization are scarce. Nevertheless, a correct identification of this nematode is necessary since several species of this genus are in quaranti ne in Latin America. The genome regions ITS and 28S are most used for identification of Bursaphelenchus species. These regions were used herein to characterize brazilian and colombian populations of B. cocophilus. The phylogenetic analysis of those regions proved that the population studied belonged to B. cocophilus species. Studies on the region 28S segment D2/3 led to the formation of monophyletic group from the sequences of all populations of Brazil and Colombia including genbank sequences of the Costa Rica and Honduras populations. In the B. cocophilus clade, three subclades were formed: in the first one grouped the colombian populations only; in the second, grouped the brazilian and costa rican populations and in the third, based clade, stayed the honduras populations alone. The region ITS1/2 was not enough to separate brazilian and colombian populations, however generated one clade separating those populations from others Bursaphelenchus species and also, as sister clade, the B. pratzeri. A specific primer was developed for rapid detection of B. cocophilus. Our work indicates that B. cocophilus populations from Brazil and Colombia were, possibly, originated from single introduction due to a low genome variability encountered.